Religious and Social Dimensions of The Nyadran Tradition In Watualang Village: A Study of Pluralism and National Identity - Hikmawati, Hanifah (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2026)
This study examines the Nyadran tradition in Watualang Village, Ngawi District, East Java, as an arena of tradition contestation in the modern era, reflecting the dynamics of pluralism and nationalism. Employing an interpretative descriptive qualitative approach through in-depth interviews, participatory observation, and document analysis, the study is analyzed through the lens of Richard Rorty's pragmatism. The findings reveal that Nyadran in Watualang Village is an annual ritual performed Jumat Pahing in the month of Dzulhijjah at the Gupito Sari grave, with the latest innovation being a procession of two gunungan (cone-shaped offerings) symbolizing gratitude for the earth's yield. The ritual brings together the santri and abangan in a shared space representing social harmony amid differences in religious belief and practice. Although the community continues to embrace metaphysical aspects such as the existence of the danyang (village spirit guardian) and the threat of pamali (taboo) as justification for the tradition (metaphysical correspondence), the Nyadran practice also demonstrates pragmatic functions in strengthening social solidarity, community cohesion, and nationalism. This tension between metaphysical justification and pragmatic function is precisely what lends the Nyadran tradition its vitality, where in the sacred dimension and social solidarity operate in tandem. This study contributes to the debate in Javanese Islam studies by shifting the focus from the question of 'whether Nyadran is Islamic or not' toward an understanding of how local rituals function socially and politically as resources for social cohesion in Indonesia's plural society.